(untitled) (قضايا سياسية, 2022)
The relationship and mutual influence between economic factors and political stability is a complex interrelationship. The effects of this relationship may appear directly or indirectly in the short or long term. The economic recovery of a country helps stabilize the political system, while the economic difficulties negatively affect In the degree of acceptance of the peoples of the ruling regimes prevailing in their country, on the other hand, we note that political stability is a major factor in the economic recovery, and vice versa, when the political problems of a country is clearly reflected on the economic performance of the country, p What are the economic factors, one of the main causes of political instability, and we will address in this research the concept of political stability and political instability, and the most important economic factors affecting the political instability in Iraq.